Stressful Life Events and Reward Processing in Adults: Moderation by Depression and Anhedonia - Min, Sung; Mazurka, Raegan; Pizzagalli, Diego A.; Whitton, Alexis E.; Milev, Roumen V.; Bagby, R. Michael; Kennedy, Sidney H.; Harkness, Kate L. (Depression and Anxiety, 2024)
Background. Exposure to acute stress is associated with reduced reward processing in laboratory studies in animals and humans. However, less clear is the association between reward processing and exposure to naturalistic stressful life events. The goal of the current study was to provide a novel investigation of the relation between past 6-month stressful life events and reward processing, and the extent to which this relation was moderated by depression diagnostic status and state symptoms of anhedonia. Methods. The current study included a secondary analysis of data from 107 adults (37 current-depressed, 25 past-depressed, 45 never-depressed; 75% women) drawn from two previous community studies. Past 6-month stressful life events were assessed with a rigorous contextual interview with independent ratings. Response to monetary reward was assessed with a probabilistic reward task. Results. Among current-depressed participants, and among both current- and past-depressed participants with high levels of anhedonia, greater exposure to independent life events outside of individuals’ control was significantly associated with poorer reward learning. In direct contrast, among those with low levels of anhedonia, greater exposure to independent life events was significantly associated with a greater overall bias toward the more frequently rewarded stimulus. Conclusions. Results suggest that depression and anhedonia are uniquely associated with vulnerability to blunted reward learning in the face of uncontrollable stressors. In contrast, in the absence of anhedonia symptoms, heightened reward processing during or following independent stressful life event exposure may represent an adaptive response.